The effect of Fenugreek oil (Iraqi fenugreek seeds' extract) on Adult uncoupled rats and mice ovaries Histological and hormonal assay - AL- chalabii, Israa M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Fenugreek herb is one of the most abundant plants in our country. The dried ripe seeds of this plant are the effective medicinal part the plant.Aim of the work: The aim of this study is to determine the pharmacological effect of a new chemical substance that has been extracted from crude fenugreek seeds which has a hormonal like action and to assess the safety of this experimental material in order to recommend it in future as a stimulator for ovulation or a contraceptive pill.Materials and Methods: Sixty uncoupled female rats and mice were enrolled in this study, categorized into groups as mentioned in the text. Prolactin, estradiol and progesterone serum levels where measured for all groups. Histological and statistical analytical methods were applied to identify the increase in the folliculogenis process within the ovaries of the studied animals. Results: There was an increase in folliculogenesis process in all experimental groups studied when compared to the control (group II, then group III respectively in ascending way). Thesefindings were confirmed histologically as shown in the figures presented in the text showing the mean number of various ovarian components of experimental groups69.2±8.2 in groupli and 103.9 ±14.7 counted as the mean values these componentsand compared to the mean values of the control group which is equal to35.2 t 10.3. Hormonal assay levels, showed increase in the serum levels of hormones studied (prolactin, estradiol & progesterone) in all the experimental groups with percentage in elevation of prolactin in groups II and III were(57% and 44.3% respectively). While the percentage of elevation of estradiol in groups II and III were (76% and 65% respectively). And the percentage of elevation in progesteronehormone in groups II and III were (78% and 73% respectively). The significancy of this elevation was more significant in groups IIR and IIM than. As shown in Figures (12,13, & 14). Conclusion: It has been concluded that fenugreek oil has a significant effect on folliculogenesis process within the ovary and it increases sex hormones level in theblood due to its wide biochemical effective components.